Rapid endocytosis coupled to exocytosis in adrenal chromaffin cells involves Ca2+, GTP, and dynamin but not clathrin. - Artalejo, C R (1995)
Rapid endocytosis (RE) occurs immediately after an exocytotic burst in adrenal chromaffin cells. Capacitance measurements of endoocytosis reveal that recovery of membrane is a biphasic process that is complete within 20 sec. The ultimate extent of membrane retrieval is precisely controlled and capacitance invariably returns to its prestimulation value. The mechanism of RE specifically requires intracellular Ca2+; Sr2+ and Ba2+ do not substitute, although all three cations support secretion. Thus the divalent cation receptors for RE and exocytosis must be distinct molecules. RE is dependent on GTP hydrolysis; it is blocked by GTP removal or replacement with guanosine 5'-[gamma-thio]triphosphate. In the presence of GTP, multiple rounds of secretion followed by RE could be elicited from the same cell. RE requires participation of dynamin, a guanine nucleotide binding protein, as revealed by intracellular immunological antagonism of this protein. Intact microtubules may be essential, as nocodazole also blocked RE. Whereas anti-dynamin antibodies blocked RE, anti-clathrin antibodies did not, suggesting that clathrin-coated vesicles are not involved in this form of endocytosis. RE may represent the initial step in the rapid recycling of secretory granules in the chromaffin cell.